Migrantes do Sul na Amazônia mato-grossense : o CTG Porteira Aberta - Siebiger, Elizângela Gomes dos Santos (2020)
The scenario of the state of Mato Grosso is extremely rich in terms of its cultural diversity. This research is concerned with investigating a portion of this diversity by focusing on migrants coming from southern Brazil to the Midwest. The work brings the concern to analyze the sociability experienced by this particular social group within a Center of Gaucho Traditions, in Colíder, and its processes of historical formation, the construction of the idea of belonging and the triggering of cultural manifestations, unveiling elements of everyday life, as well as bringing reflections on urban dynamics. To accomplish this work, we started from an ethnographic study. Using life stories to access memories about the adaptation process, as well as the formation of the city of Colíder. As a methodological strategy was also adopted the use of participant observation at the Center of Gaucho Traditions Open Door.